Competitive Benchmarking of Universiti Utara Malaysia’s Performance against the Performance of Selected Malaysian Universities - Engku Abu Bakar, Engku Muhammad Nazri; Suppiah Shanmugam, S. Kanageswari; Abd Manaf, Nor Aziah (Inderscience Publishers, 2022)
This paper reports on a competitive benchmarking study to gauge where Universiti Utara Malaysia (UUM) stands with respect to six other top universities in Malaysia, based on the perception of the universities’ stakeholders (potential employers) on ten different relevant performance attributes. Compromised-AHP was used to calculate the performance score obtained by each university with regards to each performance attribute. The findings, based on 92 evaluations received revealed that although UUM was only recently ranked fifth among the seven universities selected for this study (based on the 2019 Times Higher Education Asia University Rankings), UUM surprisingly scored comparatively well in all the performance attributes except for one performance attribute, the English language proficiency of the graduates. However, although UUM is perceived to comparatively performing better than the other six universities, overall, the actual performance is perceived to be only at the level of slightly above average. The findings are very beneficial to UUM in the sense that by knowing which aspects that UUM is perceived by the potential employers to be lacking and require further improvements, appropriate strategies can be formulated and undertaken by the UUM management to strengthen its performance.